PENGARUH STRATEGI MARKETING MIX JASA TERHADAP KEPUTUSAN PEMBELIAN KARTU PERDANA PRABAYAR XL DI KOTA TANGERANG - Sudirman, Sudirman (Proceedings of KNASTIK, 2013)
The aim of this study is to determine, (1) The effect of the product purchase decision XL prepaid SIM Card in Tangerang, (2) Effect of price on purchase decisions XL prepaid SIM Card in Tangerang, (3) Effect of distribution of prepaid SIM Card purchase decisions XL in Tangerang,(4) Effect of promotion to the premier prepaid card purchasing decisions XL Tangerang, (5) Effect of employees' purchasing decisions XL prepaid SIM Card in Tangerang, (6) Effect of physical evidence against the decision of purchasing a prepaid SIM Card XL in Tangerang, (7) The effect of the decision process of purchasing a prepaid SIM Card XL in Tangerang. The population in this study were all customers who use prepaid cards XL in Tangerang during the past year or so. The number of samples in this study were 200 respondents. Analytical techniques used in this research is descriptive analysis and pathway analysis (path analysis) by using sampling techniques areaccidental sampling. Based on the results of hypothesis testing indicate that (1) Variable product does not significantly influence the purchase decision(2) Variable ratesdo not significantly influence the purchase decision (3) Variable distribution significantly influence the purchase decision (4) the promotion variable does not significantly influence the purchase decision ( 5) Variable employees significantly influence the purchase decision (6) The variables of physical evidence does not significantly influence the purchase decision (7) The variables significantly influence the purchase decision. The results showed that (1) The direct effect is greater than the indirect effect of the variable distribution of the purchasing decision (2) The direct effect is greater than the indirect effect of the variable employee to purchase decisions (3) The direct effect is greater than the indirect effect of variable to the purchase decision process.